Assessing Student Characteristics With The Right Instruments: An Important Pathway To Implementing A Merdeka Curriculum In Indonesia - Elfitra, Elfitra; Armanto, Dian; Dewi, Izwita (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The implementation of Indonesia's Merdeka Curriculum necessitates a comprehensive understanding of student characteristics to support personalized learning experiences. This study explores the evaluation of student characteristics, assessment instruments, and their application in improving the learning process within the Merdeka Curriculum framework.To examine the evaluation of student characteristics, various assessment instruments, factors influencing instrument selection and application, and the benefits of evaluations in enhancing the learning process. This qualitative study employs a systematic literature review. The research steps include: 1) Collecting relevant literature from academic databases, focusing on journal articles, books, and government regulations related to the Merdeka Curriculum and student assessment; 2) Analyzing collected materials using content analysis techniques; 3) Synthesizing key themes and findings; 4) Validating results through data source triangulation and peer review. The study identifies key student characteristics for assessment, including cognitive abilities, learning readiness, motivation, learning styles, self-regulation, and social-emotional skills. Various assessment instruments are discussed, such as standardized tests, evaluation scales, performance-based assessments, interviews, and observations. Factors influencing instrument selection include assessment goals, student characteristics, and available resources. The benefits of student characteristic evaluations include informing adaptive instruction, providing targeted support, and monitoring student progress. Effective evaluation of student characteristics is crucial for implementing the Merdeka Curriculum and supporting student-centered learning in Indonesia. The study emphasizes the need for a shift towards process-oriented assessment and highlights the importance of collaboration among educational stakeholders to create an inclusive learning environment.